Eficacia del hierro sacarato y hemotrasfusión en el tratamiento de la anemia moderada y severa en pacientes del Hospital Regional de Loreto, 2019 - Gárate Barbarán, Jesse Jhossimar (2022)
OBJETIVE: To determine the efficacy of Iron Saccharate and blood transfusion in the treatment of moderate and severe anemia in patients treated at the Regional Hospital of Loreto, 2019. MATERIALS AND METHODS. Correlational, descriptive, prospective, and cross-sectional study. All adult patients 18 to 65 years of age, of both sexes, with a diagnosis of moderate or severe anemia treated at the Regional Hospital of Loreto, year 2019. The Data Collection Form was used, which had a validity of 97,5%, through the Expert Judgment method; It had a reliability of 92,6%, according to Cron Bach's alpha. The data were analyzed using the SPSS 10.0 statistical program. In the elaboration of the tables and statistical graphs, the Excel 2000 program was used. RESULTS: 85,4% of the study patients had moderate anemia and 14,6% had severe anemia. In patients with moderate anemia, the efficiency of blood transfusion was 96,3%, and that of iron saccharate was 93,4%: in men, the efficacy of both iron saccharate and blood transfusion was similar (93,8%); in non-pregnant women, the efficacy of both iron saccharate and blood transfusion was also similar (94,7%); in pregnant women, the efficiency of blood transfusion was 98,1% and that of iron saccharate was 92,3%. In severe anemia, the efficiency of blood transfusion was 77.8%, and that of iron saccharate was 11,2%: in men, the efficiency of blood transfusion was 75,0%, and that of iron saccharate was 25,0%; in non-pregnant women, the efficiency of blood transfusion was 100,0% and that of iron saccharate was 20,0%; and, in pregnant women, the efficiency of blood transfusion was 62,5% while the efficiency of iron saccharate was zero (0%). CONCLUSIONS: Iron saccharate was effective in 93,4% of patients with moderate anemia and in 11,2% of patients with severe anemia. Blood transfusion was effective in 96, 3% of all patients with moderate anemia and in 77,8% of patients with severe anemia.